Oligoclonal Bands in Multiple System Atrophy: Case Report and Proposed Mechanisms of Immunogenicity - Neilson, Lee E.; Hollen, Christopher; Hiller, Amie; Wooliscroft, Lindsey (Frontiers in Neuroscience, 2022)
Multiple System Atrophy (MSA) is a neurodegenerative disease with heterogeneous manifestations and is therefore difficult to diagnose definitively. Because of this, oftentimes an extensive workup for mimickers is undertaken. We herein report a case where the history and cerebrospinal fluid (CSF) findings of oligoclonal bands suggested an inflammatory disorder. Immunomodulatory therapy failed to ameliorate symptoms or alter the trajectory of continued physical decline, prompting re-visitation of the diagnosis. Oligoclonal bands, while generally viewed as specific to multiple sclerosis or other inflammatory conditions, may be seen in other disease processes. Therefore, this finding should not exclude consideration of neurodegenerative disease.